PENGARUH AUDIT SEKTOR PUBLIK TERHADAP PENGEMBANGAN AKUNTANSI PEMERINTAHAN DI INDONESIA - PUJIONO, PUJIONO; JATI, I KETUT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 2 No 2 (2007))
This article discusses about the increasing public sectors audit, particularly pertain tothe government sector in Indonesia. The increasing auditing role in public sectors must bebalanced with developed governmental accounting. Thus, retrieving public sector auditingstandards can ensure adequate governmental financial administration. SA-APFP 1996 createdby BPKP need to be revised in part that supposed to be of importance. Financial accountingsystem which be based to the UYHD system must be changed and adapted to publicrequirements. The last part of the article consists of conclusion and suggestion for retrieval inincreasing quality of audit public sector and governmental accounting application in Indonesia.
Keywords: public sectors audit, government, governmental accounting, UYHD system